Digital Convergence in Contemporary Newsrooms: Media Innovation, Content Adaptation, Digital Transformation, and Cyber Journalism - Medeiros Neto, Benedito and Ghinea, George and Amaral, Inês (Springer International Publishing, 2021)
This book explores the dynamic landscape in contemporary newsrooms across three continents by investigating the impact that the processes of searching, processing, and distributing data and information and the use of big data, with secure, automatic, and agile retrieval of information all have in this context. Journalistic organizations have undergone digital transformations, and only those implementing accurate transformations survive. In so doing, the book addresses the fields of e-Communication, Computer Science, and Information Science and other areas of the authors’ expertise. The first five chapters focus on technical visits to investigate newsrooms’ productive routines and flows in major dailies from Brazil, Costa Rica, and England. The remaining chapters consider that the news production routines are cooperative and distributed and at the same time need to be managed from different perspectives to support the convergence of digital media. Last but not least, the book also identifies an increase in ICT-based tools, with an increasing connection from new media combined with the growing trend of digital economy practices as important factors in the new landscape of digital journalism.
https://katalog.adlr.link/Record/51-9783030744274